TRANSLANGUAGING AS EMOTIONAL SCAFFOLDING: REDUCING SPEAKING ANXIETY AND FOSTERING ORAL PROFICIENCY IN AN INDONESIAN EFL CONTEXT - Yopi Indah Susila; Slamet Asari (Indonesian EFL Journal, 2025)
Speaking anxiety is one of the most common challenges in English as a Foreign Language (EFL) learning, particularly in multilingual settings like Indonesia. This study investigates how translanguaging-based emotional scaffolding (TES)—a combination of flexible language use and emotional support—can reduce speaking anxiety and improve speaking performance among learners in Kampung Inggris Pare. Using a qualitatively driven mixed-method design, data were collected from 28 students through questionnaires and reflective responses. Quantitative data were analyzed descriptively, while qualitative data were examined thematically. The results show that most learners used their first language to plan ideas before speaking English and received consistent emotional support from tutors. Translanguaging helped students reduce linguistic pressure, while emotional scaffolding through praise, empathy, and supportive feedback created a comfortable learning atmosphere. These combined practices effectively lowered anxiety, increased confidence, and improved speaking fluency. A few learners, however, preferred full-English instruction, believing it accelerated fluency. Overall, the study concludes that TES can balance both emotional and cognitive aspects of language learning and serves as an effective approach to build confidence, motivation, and communicative competence in multilingual EFL environments. These findings highlight the importance of integrating emotional and linguistic support in EFL pedagogy. Translanguaging-based emotional scaffolding offers a sustainable pathway for educators to foster confidence, reduce anxiety, and create more inclusive learning environments in multilingual contexts.